Gambaran inklinasi insisivus sentral maksila pada pasien ortodonti usia 18-25 tahun berdasarkan analisis sudut U1-SN - Maria Fidela Maringka, Stella; Juliani Hardja Buntara, Magdalena (Jurnal Kedokteran Gigi Terpadu, 2024)
Background: Cephalometry is an essential diagnostic tool to establish a diagnosis and develop a comprehensive treatment plan. The cephalogram commonly used is a lateral cephalogram which aims to evaluate the relationship of skeletal bones, teeth, and soft tissue. Cephalometric analysis of hard tissue is divided into three, namely skeletal analysis, dentoalveolar analysis, and dental analysis. The dentoalveolar analysis serves to evaluate the relationship of the central incisors to the cranial base and mandible. The inclination of the maxillary central incisors towards the cranial base was measured using the U1-SN angle parameter. The inclination of the maxillary central incisors plays a role in shaping the facial profile and achieving ideal occlusion. Objective: To determine the inclination of the maxillary central incisors based on U1-SN angle analysis in patients aged 18-25 years at RSGM-P FKG Usakti. Method: Descriptive observational study with a cross-sectional design on lateral cephalograms of orthodontic patients aged 18-25 years at RSGM-P FKG Usakti in 2021-2022. Results: The average value of the patient's U1-SN angle was 109,86o with a standard deviation of 7,34o. Conclusion: This study showed that the patient's maxillary central incisors were proclined with an average value of 109,86o ± 7,34o.